Interpreter-mediated aphasia assessments: Mismatches in frames and professional orientations. (3rd April 2019) - Roger, Peter; Code, Chris
Abstract : A setting which presents special challenges for interpreter- mediated communication is the speech pathology clinic, particularly when the encounter involves the assessment of aphasia. Drawing on a corpus of five interpreter-mediated assessments of aphasia in speakers of a range of languages (Cantonese, Greek, Tagalog and Vietnamese), this paper presents the findings of an interactive framing analysis of the corpus, focusing on illustrative extracts from two of the encounters. Analysis reveals that while the interpreters are frequently oriented towards issues of 'meaning' or 'content', the speech pathologists are generally oriented to issues of 'form'. This is evident from the fact that the speech pathologists frequently question the interpreters about the ways in which the speaker's language is abnormal. The interpreters, however, tend to respond to such questions with reference to their impressions of the person's intended meaning. It is argued that these differences in orientation can be explained by the different professional knowledge schemata of speech pathologists and interpreters and the fundamentally 'uninterpretable' nature of many of the speakers' utterances. This lack of shared understanding makes the interaction inefficient, and frequently results in a situation where the person with aphasia is put 'on hold'. The paper concludes with a discussion of some practical implications for the conduct of interpretermediated aphasia assessments.